Biodiversity and distribution of the deep-sea fauna in the Sea of Japan and in the Kuril-Kamchatka Trench area with focus on Isopoda as a model organism - Elsner, Nikolaus (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2014)
The aim of this dissertation is to analyze the diversity and distribution of the deep-sea fauna of the Northwest Pacific, more specifically the Sea of Japan and the abyssal plain adjacent to the Kuril-Kamchatka Trench. Deep-sea benthic structure of both areas is analyzed at higher taxonomic level and in greater detail exemplarily for isopods at species and population level. The main focus herein lies on the diversity recorded for each of the areas and the comparison between both. Two deep-sea expeditions were conducted in order to obtain samples from the Sea of Japan and the Kuril-Kamchatka Trench with the Russian research vessel Akademik M. A. Lavrentyev in 2010 (Sea of Japan Biodiversity Studies; SoJaBio) and the German research vessel Sonne in 2012 (Kuril-Kamchatka Biodiversity Studies; KuramBio), respectively. Additionally, samples from the Kuril-Kamchatka Trench area, conducted with the Russian research vessel Vityaz in the 1950s, were used for further comparisons. In conclusion, the studies conducted in the framework of this thesis improved our knowledge and understanding of the deep-sea fauna of the Northwest Pacific, namely the Sea of Japan and the abyssal plain southeast of the Kuril-Kamchatka Trench. The former is impoverished due to its geological history and characteristics, the latter exhibits high diversity, which can mainly be explained by the old age of the Pacific, the connectivity of the area with adjacent basins and the Oyashio current bringing nutrient-rich waters into the area. Furthermore, the populations of three species of isopods in part co-occurring in the Sea of Japan do not share the same population structure and reproductive mode, which might suggest avoidance of direct competition and occupation of different ecological niches. This could lead to differences in distributional patterns and may help to explain the distributional limits and possibilities of individual species, both bathymetrically and geographically. Das Ziel dieser Dissertation ist die Analyse der Diversität und ...